Monosomy 21 Seen in Live Born Is Unlikely to Represent True Monosomy 21: A Case Report and Review of the Literature - Trent Burgess; Lilian Downie; Mark D. Pertile; David Francis; Melissa Glass; Sara Nouri; Rosalynn Pszczola (Case Reports in Genetics)
We report a case of a neonate who was shown with routine chromosome analysis on peripheral blood lymphocytes to have full monosomy 21. Further investigation on fibroblast cells using conventional chromosome and FISH analysis revealed two additional mosaic cell lines; one is containing a ring chromosome 21 and the other a double ring chromosome 21. In addition, chromosome microarray analysis (CMA) on fibroblasts showed a mosaic duplication of chromosome region 21q11.2q22.13 with approximately 45% of cells showing three copies of the proximal long arm segment, consistent with the presence of a mosaic ring chromosome 21 with ring instability. The CMA also showed complete monosomy for an 8.8 Mb terminal segment (21q22.13q22.3). Whilst this patient had a provisional clinical diagnosis of trisomy 21, the patient also had phenotypic features consistent with monosomy 21, such as prominent epicanthic folds, broad nasal bridge, anteverted nares, simple ears, and bilateral overlapping fifth fingers, features which can also be present in individuals with Down syndrome. The patient died at 4.5 months of age. This case highlights the need for additional studies using multiple tissue types and molecular testing methodologies in patients provisionally diagnosed with monosomy 21, in particular if detected in the neonatal period.